Learning Ohm's Law through Electric Puzzle Media - Adam Malik; Muhamad Dudi Asyidik; Kusmi Heni Nursamsika; Rifadiyah Nurul Khotimah; Rismaya Fitriyani (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
Electrical circuit components or electronic circuits can be connected with series and parallel circuits. The arrangement of the circuit can affect the desired lamp characteristics. This study aims to measure the magnitude of resistance in an electrical circuit, analyze the flame of a series and parallel resistance, explore the relationship between voltage (V) with current (I) in series and parallel circuits. The method research used quantitative methods based on the problem-solving laboratory. The laboratory equipment used consists of a battery, incandescent lamps, resistors, stacking and zinc puzzles, multimeters, jumper cables. The laboratory equipment assembled and measured the intensity of the light produced using the physics toolbox application on a handphone. The data has obtained, then presented in a table and calculated using a formula, and analyzed the uncertainty in its measurement. The result showed the intensity of light in a series of different magnitude, the power of the light was more significant in lamp one, and in lamp two, the power was smaller. The intensity of the light in the parallel circuit was the same magnitude. Still, the value of the light intensity in the parallel circuit was smaller than the intensity in the lamps arranged in series. The relationship between voltage (V) and current (I) in both series and parallel circuits was comparable and directly proportional. Thus, the developed series of electric puzzles can adequately explain Ohm’s law. Ohm’s law learning with electric puzzles can be used in school and learned by students quickly.